Health and Economic Growth - David E. Bloom; Michael Kuhn; Klaus Prettner (Institute of Labor Economics (IZA), 2018)
The positive cross-country correlation between health and economic growth is well-established, but the underlying mechanisms are complex and difficult to discern. Three issues are of central concern. First, assessing and disentangling causality between health and economic growth is empirically challenging. Second, the relation between health and economic growth changes over the process of economic development. Third, different dimensions of health (mortality vs. morbidity, children's and women's health, and health at older ages) may have different economic effects.
Keywords: I10; J13; J24; 330; economic well-being; economic development; poverty traps; productivity; health; longevity; living standards; neoclassical and R&D-based growth